Hukum Sutrah menurut Imam al-Syaukani (Studi Kitab Nail al-Authar) - Idam, Saadal Jannah; Rosmita; Kamus; Suaib, Husnawati (STAIN MAJENE, 2024)
Sutrah is an object in front of a person who is praying to prevent others from passing in front of him. Sutrah is prescribed because the Prophet SAW maintained it in every prayer. However, scholars have different opinions about its law. Some say it is sunnah and some consider it obligatory. This study aims to determine the law of sutrah according to Imam al-Syaukani in his book Nail al-Autar. The problems raised are; first, what is the concept of sutrah in prayer. Second, what is the law of sutrah in Islam. Third, what is the law of sutrah according to Imam al-Syaukani in the book Nail al-Autar. This study uses a type of qualitative research that focuses on text studies (library research), and uses normative and historical juridical approaches. The results of the study show that; First, the concept of sutrah in prayer is everything that is in front of the person praying, it can be in the form of a stick, arrow, tree, wall or the like to prevent people from passing in front of him. Second, scholars have different opinions about the law of sutrah in sharia. Imam al-Syaukani said it was mandatory. The majority of ulama consider the sutrah to be the sunnah of muakadah. Third, according to Imam al-Syaukani, the law of sutrah is obligatory because the sutrah is a syar'i cause that prevents prayers from being canceled due to the passing of mature women, donkeys and black dogs. Imam al-Syaukani argued with the hadith lafadz